Exploring Colonial Historiography A Study on John Th. Petrus Blumberger and His Writings on the Internal Conflicts of Sarekat Islam (1917-1923) - Nisrina Auliffia Rachman; Mohammad Il Badri (Criksetra: Jurnal Pendidikan Sejarah, 2025)
This research aims to uncover the persona of John Theodoor Petrus Blumberger and his writings that depict the internal conflicts within Sarekat Islam (SI) during the period of 1917-1923, which constitute an important part of the history of the Indonesian national movement. This study is a qualitative research in the form of a literature review. The method employed in this research is the historical method, encompassing steps such as Heuristics, Verification, Interpretation, and Historiography. Furthermore, this research is presented through descriptive analysis. The analysis results indicate that Blumberger, as a government official, portrays the dynamics of Sarekat Islam influenced by the Socialist Communist Ideology propagated by the local SI of Semarang. Additionally, Blumberger's historiographical approach is neither skeptical nor provocative towards Sarekat Islam, as he merely presents his findings in accordance with the available archives. This approach is also influenced by the governmental background situated within the ethical political atmosphere, which led Blumberger to emphasize the role of the government as the protector of all the people in the colony in his works.